Integration in the German-Polish border region - Status Quo and Current Developments - Silvia Stiller (European Regional Science Association (ERSA), 2003)
National borders within the European Union have significantly lost importance during the last decades. That is because the costs for the movement of goods, services, production factors and information across borders continuously decreased in the course of advancing integration. Lower distance costs and almost meaningless national borders open up best conditions for intensifying trade, factor mobility and the international and interregional division of labour. Thus, European integration is likely to affect the economic geography within the participating countries. Most probably, among other factors, also a region's relative geographical position in the whole integration area impacts the regional effects of European integration. Marked by a particular geographical position are those regions which are located along the national borders among integrating countries and thus are from the geographical perspective the focal point of integration. A striking feature of those inner border regions of the EU is that their relative geographical position is immensely altered in the course of integration: It changes from a peripheral position on the national scale to a more or less central one within the whole integration area. The paper investigates economic structure and development of the EU inner border regions. The empirical analysis covers the time period from 1980 to 1998 and deals with employment, GDP and population density and development The analysed question is whether there are - measured by these indicators - systematic differences in economic development among inner border regions and the rest of their respective country. The analysis of the EU's inner border regions is first of all interesting regarding historical and prospective developments among current European Union member states. Furthermore, plenty of inner border regions will emerge in the course of EU Eastern enlargement, for example along the border between Germany and Poland.
Keywords: 330